2006
DOI: 10.1002/jmri.20656
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of microstructural damage in the brains of professional boxers: A diffusion MRI study

Abstract: Purpose: To investigate and localize cerebral abnormalities in professional boxers with no history of moderate or severe head trauma. Materials and Methods:Diffusion tensor imaging (DTI) was used to determine the apparent diffusion coefficient (ADC) and fractional anisotropy (FA) in the brains of 81 professional male boxers and 12 male control subjects. Voxel-based analysis (VBA) of both the diffusion and anisotropy values was performed using statistical parametric mapping (SPM). From this objective analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 22 publications
4
68
2
3
Order By: Relevance
“…Recall that Viano et al (2005b) showed that the corpus callosum was one of the brain regions receiving the biggest strain effect in concussion. Similarly, Chappell et al (2006) using DTI methods demonstrated similar white matter pathology in a group of 81 professional boxers. These studies focused on professional boxers without known neurological impairment, otherwise they would not be boxing, and show that sensitive MRI methods do detect with a higher frequency abnormalities of white matter.…”
Section: Pathophysiology Of Concussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Recall that Viano et al (2005b) showed that the corpus callosum was one of the brain regions receiving the biggest strain effect in concussion. Similarly, Chappell et al (2006) using DTI methods demonstrated similar white matter pathology in a group of 81 professional boxers. These studies focused on professional boxers without known neurological impairment, otherwise they would not be boxing, and show that sensitive MRI methods do detect with a higher frequency abnormalities of white matter.…”
Section: Pathophysiology Of Concussionmentioning
confidence: 67%
“…Likewise, complicated mTBI is more likely to have positive neuroimaging findings (Levine et al, 2006;McAllister et al, 2001;Vorst et al, 2007) and significant residuals (Kennedy et al, 2006). If boxing is considered a model for detecting "pre-clinical" or asymptomatic brain injury, recent diffusion tensor imaging studies have demonstrated abnormalities in boxers (Chappell et al, 2006;Zhang et al, 2006b). Thus, animal and human studies support the contention of injury on a continuum, implicating that understanding the variables that relate to severity of injury are likely very important in understanding neuropsychological sequelae (see Wilde et al, in press;Lewine et al, 2007).…”
Section: Is Brain Injury On a Continuum: Concussion R Severe Tbi?mentioning
confidence: 99%
“…18 A limited number of studies have investigated diffusion changes in the white matter of fighting athletes. 7,8,19 These studies found that among fighting athletes, whole-brain diffusion is increased, 8 FA is reduced in the genu and splenium of the corpus callosum and the posterior internal capsule, 7 and FA is reduced and ADC increased in the lower brain, the splenium of the corpus callosum, and the lateral and dorsolateral cortical regions. 19 Although these studies used age-and sex-matched control groups, variations among fighters in number of fights and number of knockouts have not been fully investigated.…”
mentioning
confidence: 98%
“…7,8,19 These studies found that among fighting athletes, whole-brain diffusion is increased, 8 FA is reduced in the genu and splenium of the corpus callosum and the posterior internal capsule, 7 and FA is reduced and ADC increased in the lower brain, the splenium of the corpus callosum, and the lateral and dorsolateral cortical regions. 19 Although these studies used age-and sex-matched control groups, variations among fighters in number of fights and number of knockouts have not been fully investigated. Zhang et al 8 found that the number of hospitalizations for boxing injuries was positively correlated with the peak of the Gaussian-fitted brain tissue compartment in a whole-brain diffusion histogram in 24 professional boxers.…”
mentioning
confidence: 98%
“…Such injuries can be encountered more commonly particularly among boxers (7). General health condition and sport success of the athletes can be adversely affected.…”
Section: Discussionmentioning
confidence: 99%